The expression of heparanase in term and preterm human placentas. (12th December 2022) - Naeh, Amir; Hantisteanu, Shay; Meisel-Sharon, Shilhav; Boyango, Ilanit; Hallak, Mordechai; Gabbay-Benziv, Rinat
Abstract: Purpose: Heparanase is an endo- β -glucuronidase that cleaves side chains of heparan-sulfate proteoglycans, an integral constituent of the extra cellular matrix. The abundance of heparanase in placental trophoblast cells implies its role in the processes of placentation and trophoblast invasion. This study aims to explore the involvement of heparanase in parturition and preterm deliveries (PTD). Methods: Sixteen human placentas were collected following singleton spontaneous onset term vaginal deliveries ( n  = 6), spontaneous onset preterm vaginal deliveries ( n  = 7) and term elective cesarean sections ( n  = 3). Placentas were excluded in case of any maternal chronic illness, pregnancy or delivery complications apart from PTD. Placental tissue samples were dissected, homogenized and proteins were extracted. Additionally, cryosections were prepared from the placental tissues. Heparanase expression was evaluated utilizing western blot analysis and immunofluorescence staining using heparanase specific antibodies. Heparanase expression was compared between the study groups qualitatively and quantitatively. Results: Western blot analysis results demonstrated higher expression of both pro-heparanase and heparanase in PTD placentas compared to term vaginal placentas. Accordingly, immunofluorescence staining shows elevated heparanase expression in PTD placentas compared to term vaginal placentas (5.1 ± 0.92 vs. 1.2 ± 0.18, p  < .005). Expression level of heparanase was higher in term cesarean section placentas as compared to term vaginal deliveries placentas, but did not reach statistical significance (1.8 ± 0.39 vs. 1.2 ± 0.18, p  = .06). Conclusion: This study demonstrates for the first time that preterm vaginal deliveries are associated with higher expression of heparanase in placental tissue. This may imply a direct effect of heparanase on preterm labor. Further studies should evaluate the functional role by which heparanase influence preterm delivery.